Child poverty and family transfers in Southern Europe - Manos Matsaganis; Cathal O'Donoghue; Horacio Levy; Manuela Coromaldi; Magda Mercader-Prats; Carlos Farinha Rodrigues; Stefano Toso; Panos Tsakloglou (University of Essex, Institute for Social and Economic Research (ISER), 2004)
The drive to reduce child poverty is of particular interest in southern Europe, where the subsidiary role of the State in matters of family policy has implied that programmes of public assistance to poor families with children are often meagre or not available at all. The paper examines the effect of family transfers (used broadly to include contributory family allowances, non-contributory child benefits and tax credits or allowances) on child poverty in Greece, Italy, Spain and Portugal. Using the European microsimulation model EUROMOD, the paper first assesses the distributional impact of existing family transfers and finds it is weak. The scope for policy reforms is then explored. By way of illustration, universal child benefit schemes similar to those in Britain, Denmark and Sweden are simulated. The impact of such schemes on child poverty is shown to be considerable, but their fiscal cost correspondingly substantial. The paper concludes with a discussion of key findings and policy implications.
Keywords: C81; D31; I38; 330; Child poverty; social transfers; fiscal benefits; south Europe; microsimulation